Analisis Pemanfaatan Limbah Kulit Jagung (Corn Husks) sebagai Bahan Tambah Campuran Beton Terhadap Kuat Tekan Paving Block - Rahman, Muhammad Amin; Rahman, Qarnila Ridhaniah (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The waste from corn, apart from the cobs, also includes corn husks. Various methods have been explored to process corn husk waste into something beneficial, ranging from recycling the husks to utilizing them as a material in building construction. One such application is using corn husk waste as an additive in the production of paving blocks. Paving blocks are a popular alternative for surface paving due to their ease of installation, low maintenance costs, and aesthetic appeal, making them highly sought after. The aim of this research is to examine the compressive strength of paving blocks when using corn husk waste as a mixture component. The testing was conducted when the specimens reached the ages of 7, 14, and 28 days. The research methodology consists of the following steps: 1) Material inspection, 2) Paving block mix design, 3) Specimen production, 4) Specimen curing, 5) Compressive strength testing, and data analysis. The results of the tests indicated that paving blocks with a 10% corn husk mixture, and paving blocks with a 10% corn husk mixture and 2.5% lime, yielded the highest compressive strength. When more than 10% corn husk waste was used, it caused a reduction in compressive strength. Paving blocks mixed with lime showed lower compressive strength compared to those with corn husk waste without lime.